A QUADRUPLE INTEGRAL INVOLVING THE EXPONENTIAL LOGARITHM OF QUOTIENT RADICALS IN TERMS OF THE HURWITZ-LERCH ZETA FUNCTION - Robert Reynolds; Allan Stauffer (Ural Mathematical Journal, 2022)
With a possible connection to integrals used in General Relativity, we used our contour integral method  to write a closed form solution for a quadruple integral involving exponential functions and  logarithm of quotient radicals. Almost all Hurwitz–Lerch Zeta functions have an asymmetrical zero distribution. All the results in this work are new.